An inventory system for varying decaying medicinal products in healthcare trade - Kumar, Kamal; Kumar, Neeraj; Meenu (Yugoslav Journal of Operations Research, 2021)
This paper introduces an inventory system for declining medicinal products under the effect of inflation with price-sensitive demand. Usually, pharmaceutical inventory systems assume the deteriorating rate as constant, which is insignificant and illogical because healthcare products medicines and drugs deteriorate significantly. Thus, the deteriorating rate of medicinal products is supposed to be time-dependent and to follow three-parameter Weibull distribution. The lack of commodities is permitted with the rate of partial backlogging. This research work develops a model to optimize the total average cost of the items by calculating the ordering quantity and the optimum time intervals. Finally, through a numerical example, with sensitivity analysis, we demonstrate the effect of different parameters.